Interaction and management of begomoviruses and whiteflies in weeds and horticulture crops in the state of São Paulo and survey of orthotospoviruses and associated thrips in the Arica y Parinacota region - Chile - Gorayeb, Eduardo Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Os insetos Bemisia tabaci (Gennadius) e Frankliniella occidentalis (Pergande) são pragas que conseguiram se disseminar e se estabelecer em diversas regiões do mundo. Os principais danos associados a essas pragas estão relacionados à transmissão de vírus de plantas, com destaque para os Begomovirus e Orthotospovirus. Visando contribuir com informações chave para o desenvolvimento de estratégias de manejo dessas pragas nas culturas do Tomate, Pepino e Pimentão, a presente tese contempla dois estudos envolvendo as espécies crípticas de B. tabaci Middle East-Asia Minor 1 (MEAM1) e Mediterranean (MED) no Brasil (capítulos 1 e 2), e um estudo de levantamento de tripes e orthotospoviroses na região de Arica y Parinacota, Chile (Capítulo 3). No capítulo 1, o potencial das plantas invasoras Datura stramonium e Nicandra physaloides como hospedeiras alternativas de MEAM1 e MED e do vírus Tomato severe rugose virus (ToSRV) foi estudado, mostrando que invasora N. physaloides foi uma ótima hospedeira alternativa do vírus quando associada à MEAM1, enquanto que D. stramonium contribuiu mais para a reprodução das moscas brancas. No capítulo 2, as causas relacionadas à recentes infestações de MED em pepineiro nos estados de São Paulo e Paraná foram investigadas por meio de ensaios de comparação do desempenho biológico e a preferência por hospedeiros de MEAM1 versus MED em cultivares comerciais de pepino, mostrando que a melhor performance de MED em quase todas as cultivares comerciais testadas, é um fator chave para a predominância dessa mosca no pepineiro. No capítulo 3, o Pepper necrotic spot virus, um novo vírus tentativa relacionado com o gênero Orthotospovirus é descrito na região metropolitana de Santiago (Chile), e finalmente, no capítulo 4, um levantamento de orthotospoviroses e tripes associadas foi realizado em plantas de tomate, pimentão e pimenta, na região de Arica y Parinacota (Norte do Chile), que atualmente sofre com uma epidemia de “vira-cabeça” em pimentão; mostrando a ocorrência de uma provável estirpe de Tomato spotted wilt virus capaz de infectar plantas com o gene de resistência TSW e da espécie tentativa de orthotospovirus Pepper necrotic spot virus no Chile, ambas provavelmente associadas a F. occidentalis, com ocorrência em todas as regiões amostradas.

The insects Bemisia tabaci (Gennadius) and Frankliniella occidentalis (Pergande) are pests that have managed to spread and establish in different regions of the world, disseminating several viruses, such as begomoviruses and orthotospoviruses. In order to contribute with key information for the development of management strategies for these pests in tomato (Solanum lycopersicum L.), cucumber (Cucumis sativus L.), and pepper (Capsicum spp.) crops, this thesis contemplates two studies involving the cryptic species of B. tabaci Middle East-Asia Minor 1 (MEAM1) and Mediterranean (MED) in Brazil (chapters 1 and 2), and two studies of orthotospoviruses and thrips in Chile (Chapter 3 and 4). In chapter 1, the potential of invasive plants Datura stramonium and Nicandra physaloides L. (Gaertn.) as alternative hosts of MEAM1 and MED and for the tomato severe rugose virus (ToSRV) was studied, showing N. physaloides as a great alternative host of the virus when associated with MEAM1, whereas D. stramonium contributed more with the whitefly reproduction. In chapter 2, the causes related to recent MED infestations in cucumbers observed on São Paulo and Paraná states were investigated by means of comparison of biological performance and preference tests comparing MEAM1 vs. MED in commercial cucumber cultivars, showing that MED performed better in almost all commercial cultivars tested and that the performance is a key factor for the predominance of this whitefly in cucumber plants. In chapter 3, the putative new orthotospovirus Pepper necrotic spot virus was reported for the first time in Chile, infecting bell pepper fruits, suggesting its presence in northern production areas from Chile. Finally, in chapter 4, a survey of orthotospoviruses and associated thrips was carried out on tomato, bell pepper, and chili pepper plants in Arica y Parinacota (Northern Chile), where cases of the “spotted wilt” are increasing. The results showed the occurrence of an isolate of tomato spotted wilt virus, capable of infecting plants with the Tsw resistance gene, and the putative orthotospovirus pepper necrotic spot virus in Chile, both probably associated with F. occidentalis, occurring in all sampled locations.
Interação e manejo de begomovírus e moscas brancas em plantas daninhas e hortícolas do estado de São Paulo e levantamento de orthotospovírus e tripes associadas na região de Arica y Parinacota – Chile.
Keywords: Fitopatologia; Pragas agrícolas; Vírus de plantas; Virus de RNA; Phytopathology; Agricultural pests; Plant virus; RNA virus